The role of oropharnygeal receptors in thirst perception after dehydration and rehydration (Nigerian Journal of Physiological Sciences, 2021)
Summary: This study examined the effect of drinking and gargling on thirst perception (TP) in 33 young dehydrated female subjects (18-25yrs), using the visual analogue scale (VAS). Group A subjects drank, while group B gargled the fluid provided - 0.0%, 0.9% and 1.8% NaCl (7.0 ml/kg body weight of fluid). The procedure was alternated two weeks later. All subjects dehydrated for 18 hours prior to the study, and the last 12-hour urine was collected and volume recorded. Subject who provided a 12hr urine volume greater than 400ml was excluded from the study. After recording the baseline TP, and voiding the bladder, drinking/gargling was done within 5 minutes, and the subsequent TPs were recorded at 5 minutes interval for 25 minutes. Blood samples were collected before and at the end of the 30 minutes, when urine volumes were recorded. Drinking (0.0% and 1.8% NaCl) resulted in an initial decrease in thirst perception, which was statistically significant (p